Kontestasi dan Ideologi Alternatif dalam Novel Wanasitu Anni Imra’ah karya Ihsan Abdul Qudus: Analisis Hegemoni Gramsci: Contestations and Alternative Ideologies in The Novel Wanasitu Anni Imra'ah by Ihsan Abdul Qudus: Gramsci Hegemony Analysis - Iwan Saputra; Dian Puspita Sari Habib (Balai Bahasa Provinsi Papua, 2022)
This research aims to uncover the contestation and alternative ideology which is in Wanasitu Anni Imra’ah (WAI) Ihsan Abdul Qudus’s novel by using Antonio Gramsci’s theory about sociology of literature. Gramsci understands that literature is the site of the negotiation and contestation of ideology. The view bases on the notion that literature has the crucial role to maintain or keep the social order. Otherwise, literature can also act to counter the domination which has been created. By literary work, the author strives to give alternative ideology which is regarded as the solution either government or subaltern group. Of the research which was done, the researcher found that WAI novel is the articulation result of various ideologies after Egypt revolution. Patriarch is the ideology which is understood by majority of society in which the ideology as the domination basic men to women. Besides, many other ideologies are in the WAI such as Islamic, Marxism, hedonism, capitalism, nationalism, and colonialism. The contestation which is in the WAI is the respond to domination of women’s movement to get the position in power. The relation among ideologies in WAI is subordinate, correlative, and contradictive. Through WAI novel, the author attempts to offer alternative ideology as the counter hegemony to patriarch domination that is exsistensial feminism. The ideology which is offered by the author as the respond to change era and government after Gamal Abdul Nasser’s power collapsed. Existensial feminism is regarded as the bridge for women to build the social relation and power in Egypt society.